A review of different drying methods and their impact on physiochemical and functional properties of nutmeg and star anise: Impact of drying methods on properties of nutmeg & star anise - Abhiram, Gunaratnam (Journal of Spices and Aromatic Crops, 2025)
Drying is a simple method of preservation and value addition of spices. The moisture content of the spices curtails during the drying, which decreases the biological and enzymatic activity and prolongs the shelf life. The drying method significantly influenced the flavour, chemical composition, appearance, colour, and functional properties of the bioactive compounds. Several new drying technologies are being tested to improve the physiochemical properties of the nutmeg and star anise. This article reviews different solo-drying techniques, such as sun drying, solar drying, infrared and microwave drying as well as hybrid drying such as microwave and infrared-assisted drying applied to nutmeg and star anise. Further, it discusses the impact of drying methods on chemical composition and functional properties. The advantages of novel hybrid drying techniques over conventional methods are also discussed. Further, this review identifies the research gaps and future directions for drying nutmeg and star anise.